Rhetoric Devices and Ideology: A Critical Discourse Analysis of Rashida Tlaib’s Speech on Palestine Issues - Herawati, Riana; Alim, Condro Nur (PROJECT (Professional Journal of English Education), 2025)
The Palestinian issue continues to be a central focus of global political and humanitarian discourse. In the United States, support for Palestine is often met with controversy, especially within discussions of foreign policy and civil rights. This study applies a descriptive qualitative approach, utilizing van Dijk’s Critical Discourse Analysis (CDA) and Aristotle’s rhetorical appeals pathos, logos, and ethos to investigate how Rashida Tlaib, the only Palestinian-American member of Congress, employs rhetoric and ideology in advocating for Palestinian rights. The data consist of three of her speeches retrieved from YouTube. The findings reveal that pathos (39.4%) is the most frequently employed rhetorical device, followed by logos (33.3%) and ethos (27.3%). Through tragic narratives and rhetorical questions, Tlaib evokes empathy and moral urgency; through data and logical reasoning, she critiques U.S. foreign policy; and through her personal identity and alignment with social justice movements, she reinforces credibility. Ideologically, her speeches emphasize humanitarian advocacy, anti-imperialism, global solidarity, and government accountability. This study underscores the power of rhetoric in reshaping public narratives and amplifying marginalized voices in the discourse on Palestine.